Phytochemical and Antioxidant Screening in Zuriat Fruit to Improve Spermatozoa Quality: Skill Development in Biotechnology Practical Learning - Ni Wayan Sukma Antari; Ni Komang Tri Agustini (Postgraduate, University of Mataram, 2026)
Research-based practical learning is essential in biotechnology education to develop laboratory competence and apply theoretical knowledge through scientific investigation. This study aimed to integrate phytochemical screening, antioxidant activity testing, and sperm quality analysis of Hyphaene thebaica (zuriat) fruit into a biotechnology practical and evaluate its effectiveness in improving pharmacy students' learning outcomes and laboratory competence. A mixed-methods, single-group pre-experimental pre-test–post-test design was conducted involving fifth-semester Pharmacy students at the Institute of Technology and Health Bali. The practical included phytochemical screening, antioxidant activity assessment using the DPPH method, and evaluation of sperm count, motility, morphology, and viability. Quantitative data were analyzed using paired-sample t-tests, while qualitative and observational data were analyzed descriptively. Phytochemical screening identified alkaloids, flavonoids, saponins, tannins, phenolics, steroids, triterpenoids, and terpenoids, whereas quinones were absent. The extract exhibited strong antioxidant activity (IC₅₀ = 55.49 mg/L) and improved sperm count, motility, viability, and normal morphology compared with the control group. Students' learning outcomes increased significantly from 65 ± 3.5 to 85 ± 4.2 (p = 0.001), with laboratory skills rated good to very good across all assessed domains. These findings demonstrate that research-based biotechnology practicals using zuriat fruit effectively enhance students' cognitive achievement, laboratory competence, and understanding of herbal bioactive compounds